THE INFORMATION SOCIETY: SPECIFIC OF SCIENTIFIC SPACE - Рижко, Л. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article analyzes the transformation of the scientific space of information society, conditioned by formation of post-nonclassical type of rationality and pragmatic orientation of modern science and an appeal to humanitarian values.